2011
DOI: 10.1016/j.neuint.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acid unsaturation numbers on membrane fluidity and α-secretase-dependent amyloid precursor protein processing

Abstract: Fatty acids may integrate into cell membranes to change physical properties of cell membranes, and subsequently alter cell functions in an unsaturation number-dependent manner. To address the roles of fatty acid unsaturation numbers in cellular pathways of Alzheimer's disease (AD), we systematically investigated the effects of fatty acids on cell membrane fluidity and α-secretasecleaved soluble amyloid precursor protein (sAPP α ) secretion in relations to unsaturation numbers using stearic acid (SA, 18:0), ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 84 publications
6
127
1
1
Order By: Relevance
“…This positive effect of GTE and FO intake may reflect protection against MeHg-mediated oxidative damage. Furthermore, it is reported that EGCG protects neurons by suppressing production of NADPH oxidase-mediated reactive oxygen species and NADPH-d/nNOS expression, and that FO improves the fluidity of synaptic membranes (Wei et al, 2011;He et al, 2011;Suzuki et al, 1998;Yang et al, 2011;Hashimoto et al, 2006). Furthermore, Grotto et al (2011) agree that the protective effects of FO during MeHg exposure may be related to its anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 93%
“…This positive effect of GTE and FO intake may reflect protection against MeHg-mediated oxidative damage. Furthermore, it is reported that EGCG protects neurons by suppressing production of NADPH oxidase-mediated reactive oxygen species and NADPH-d/nNOS expression, and that FO improves the fluidity of synaptic membranes (Wei et al, 2011;He et al, 2011;Suzuki et al, 1998;Yang et al, 2011;Hashimoto et al, 2006). Furthermore, Grotto et al (2011) agree that the protective effects of FO during MeHg exposure may be related to its anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 93%
“…Membrane phospholipids with polyunsaturated fatty acyl chains with 4 or more double bonds have been associated with increased membrane fluidity (34)(35)(36). We investigated the influence of Them2 and PC-TP on the composition of the major ER membrane phospholipids, phosphatidylcholines (PCs) and phosphatidylethanolamines (PEs), by mass spectrometry analyses ( Figure 6, C-H).…”
Section: Disruption Of Calcium Homeostasis By Palmitic Acid Requires mentioning
confidence: 99%
“…ER membranes isolated from livers of Them2 -/-and Pctp -/-mice were enriched with unsaturated membrane phospholipids containing fatty acyl chains with 4 or more double bonds, which markedly increase membrane fluidity (36). Our results further support that the changes in the abundance of ER phospholipids must depend on the activities of enzymes that control fatty acid metabolism (e.g., acyl-CoA synthetases, thioesterases, and desaturases), as opposed to differences in the fatty acid compositions of chow and high-fat diets, which do not contain substantial contents of fatty acids containing 4 or more double bonds.…”
Section: Them2 and Pc-tp Activate Calcium/calmodulin-dependent Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…Linoleic acid can be transformed in vivo into linolenic and further into arachidonic acid. Linolenic acid is able to increase membrane fluidity and plays an important role in neuron proliferation, nerve conduction and synapse formation (12)(13)(14). Arachidonic acid is one of the most abundant polyunsaturated fatty acids in the body and is essential for maintaining the physical property and function of the membrane (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%